Extraction and Characterization of Watermelon (Citrullus lanatus) Seed Oil - Keke, Mabel; Okpo, Samson Onoriode; Anakpoha, Oghenekome Cyril (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
This study focuses on employing solvent extraction to extract and characterize watermelon (Citrullus lanatus) seed oil. The physicochemical properties of the oil were investigated to assess its potential applications in the food, cosmetic, and pharmaceutical industries. The extraction process yielded an oil content of 43%. The oil exhibited a pH value of 4.02, refractive index of 1.452 at 25 °C, and specific gravity of 0.934 at 15 °C. The boiling point, cloud point, flash point, and melting point of oil were determined as 326 °C, 7.3 °C, 289 °C, and 2 °C, respectively. The oil's viscosity was measured as 0.04072 Pa.s, and it demonstrated a non-sooty flame nature and solubility in ether. The free fatty acid contents and acid value were determined at 3.339 % and 6.678 mg KOH/g, respectively. The saponification value (S.V) and iodine value (I.V.) were 147.6315 mg/KOH/g and 88.526 mg Iodine/g, respectively. Additionally, peroxide value was 16.40 meq peroxide/g, and the oil exhibited a congealing temperature range of -14 °C to 22 °C. The oil's retention factor during chromatography was determined as 1.6 cm. Fourier-transform infrared (FTIR) analysis revealed the presence of functional groups such as hydroxyl, amine, aliphatic hydrocarbon, carbonyl, carbon-nitrogen bond, and sulfoxide groups in the oil. These findings suggest that the presence of functional groups, such as hydroxyl, amine, aliphatic hydrocarbon, carbonyl, carbon-nitrogen bond, and sulfoxide groups in watermelon oil, indicate its potential suitability for a wide range of applications in the food, cosmetic, and pharmaceutical industries.